A retrospective analysis of antibiogram on urinary isolates in a tertiary care hospital, Trivandrum, India - K., Pramodh; T., Thansila L.; S., Pushpajan K.; Jacob, Lallu Mariam (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Antimicrobial resistance among bacterial strains is an emerging problem. Urinary tract infections are one of the most common bacterial infections in humans both in the hospital and the community settings. Gram-negative bacilli are the common pathogens isolated in urine. These uropathogens have developed resistance to commonly prescribed antimicrobial agents. This severely limits the effective empirical treatment options. Objective of this study was to determine the prevalence and antibiotic susceptibility patterns of bacterial uropathogens isolated from patients attending a tertiary care hospital Trivandrum. Methods: Urine samples received for culture in the laboratory between 6 month periods was cultured in MacConkey agar and blood agar plates. The growth from urine cultures was processed for identification and antibiotic susceptibility as per standard methods. The details of urinary pathogens grown from urine samples and their Antibiogram profile were collected from the records. Results: Out of 924 specimens investigated for significant bacteriuria, 226 shows positive cultures. E.coli and Klebsiella were the predominant pathogens isolated. Antibiotics like 3rd generation cephalosporins, fluoroquinolones, and cotrimoxazole are the usual empirical treatment options, these organisms have developed resistance towards the latter which might make the empirical therapy less effective. Conclusions: Gram-negative bacilli were the predominant pathogens isolated and many were resistant to the commonly prescribed antibiotics. Routine surveillance and monitoring studies need to be constantly conducted to update clinicians on the prevalent pathogens for the rational and empirical treatment of bacteriuria. Beta-lactam beta-lactamase inhibitors, aminoglycosides, carbapenem, and nitrofurantoin showed low resistance so they should be considered as empirical treatment options.